The analysis of postgraduate education of nurses and midwives in the North-East Masovian - Palczewska, Alicja (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. The Association of Nurses and Midwives for the Promotion of the Profession and Women’s Rights OAZA organized in year 2007 a project called: «Postgraduate Education of Nurses and Midwives, which was co-financed by the European Union and the state budget. 116 nurses and midwives took part in the cost-free trainings. Aim. The objective of the paper was to evaluate the quality of postgraduate education and the factors that encourage participation in courses. Material and methods. A diagnostic survey with author questionnaires was used to conduct the research. 179 participants evaluated motivating factors and 116 - the quality of the courses. Results and conclusions. The research presents the analysis of the factors that encourage participation in various forms of postgraduate education as well as the evaluation of the quality of the courses. The opinion was based on the questionnaires filled up by the participants at the end of the training. The results indicate a variety of factors that influence on nurses and midwives to increase their professional qualifications. The evaluation of the realization of the courses is also important, and the presented research may serve for education organizers as an example of how they could use tools to evaluate the quality of their activities.